2006
DOI: 10.1182/blood-2005-08-3320
|View full text |Cite
|
Sign up to set email alerts
|

Serial measurement of BCR-ABL transcripts in the peripheral blood after allogeneic stem cell transplantation for chronic myeloid leukemia: an attempt to define patients who may not require further therapy

Abstract: (1) 36 patients were "persistently negative" or had a single low-level positive result; (2) 51 patients, "fluctuating positive, low level," had more than 1 positive result but never more than 2 consecutive positive results; (3) 27 patients, "persistently positive, low level," had persisting low levels of BCR-ABL transcripts but never more than 3 consecutive positive results; and (4) 129 patients relapsed. In 107 of these, relapse was based initially only on molecular criteria; in 72 (67.3%) patients the leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 26 publications
0
83
1
4
Order By: Relevance
“…The entire assay (RNA extraction, cDNA synthesis and Q-PCR) was performed in duplicate in separate runs. Some centers routinely perform nested reverse transcriptase PCR to confirm CMR, 8 but we and others have found that the commonly used nested reverse transcriptase PCR method, first described by Cross et al, 9 is no more sensitive than RQ-PCR in our hands, 10,11 and, therefore, nested reverse transcriptase PCR was not included in the definition of CMR that we used to determine study eligibility.…”
Section: Rq-pcr Testingmentioning
confidence: 99%
“…The entire assay (RNA extraction, cDNA synthesis and Q-PCR) was performed in duplicate in separate runs. Some centers routinely perform nested reverse transcriptase PCR to confirm CMR, 8 but we and others have found that the commonly used nested reverse transcriptase PCR method, first described by Cross et al, 9 is no more sensitive than RQ-PCR in our hands, 10,11 and, therefore, nested reverse transcriptase PCR was not included in the definition of CMR that we used to determine study eligibility.…”
Section: Rq-pcr Testingmentioning
confidence: 99%
“…A patient was considered to be in molecular relapse if over a minimum of 4 weeks the BCR-ABL/ABL ratio exceeded 0.02% in three samples, or exceeded 0.05% in two samples, or showed rising levels with the last two higher than 0.02% as reported previously. 20 Cytogenetic relapse was diagnosed if one or more Ph-positive metaphases were detected without evidence of hematologic relapse. Hematologic relapse was diagnosed in the presence of peripheral blood leukocytosis, usually with predominance of myelocytes and neutrophils in the differential count, accompanied by a hypercellular bone marrow with Ph chromosome positivity on cytogenetic analysis.…”
Section: Definition Of Relapsementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The analysis is particularly relevant in the era of imatinib therapy where the achievement of a major molecular response (MMR) is associated with a high progression-free survival. 11 The number of centres providing RQ-PCR analysis is therefore rapidly expanding and various techniques and control genes are in use.…”
Section: Introductionmentioning
confidence: 99%